1938
DOI: 10.1021/ja01277a028
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Esterification of Benzoic Acid with Methyl Alcohol Using Isotopic Oxygen

Abstract: There has been much discussion as to which linkages are broken in the two reactions: (a) the saponification of an ester, and (b) the esterification of a carboxylic acid. The first of these was studied by Polanyi and Szabo,1 who demonstrated that the saponification of amyl acetate in heavy oxygen water results in amyl alcohol of ordinary isotopic composition. The solution of the second problem, for which evidence has been inconclusive up to the present, is the subject of this paper.The formation of water by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1956
1956
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Obviously, the mechanism is consistent with Urey and Robert's experimental result. 2 This mechanism is also in agreement with the results of ester carbonyl-O 18 exchange experiments. [13][14][15][16] Conclusion DFT calculations and ESI-MS data have proved that the acidcatalyzed carboxylic acid esterification and ester hydrolysis mechanism proposed by Watson 5,6 80 years ago is incorrect.…”
Section: Proposed Acid-catalyzed Carboxylic Acid Esterification and E...supporting
confidence: 87%
See 1 more Smart Citation
“…Obviously, the mechanism is consistent with Urey and Robert's experimental result. 2 This mechanism is also in agreement with the results of ester carbonyl-O 18 exchange experiments. [13][14][15][16] Conclusion DFT calculations and ESI-MS data have proved that the acidcatalyzed carboxylic acid esterification and ester hydrolysis mechanism proposed by Watson 5,6 80 years ago is incorrect.…”
Section: Proposed Acid-catalyzed Carboxylic Acid Esterification and E...supporting
confidence: 87%
“…However, the reaction can usually reach equilibrium quickly with a small amount of concentrated sulfuric acid or hydrogen chloride as catalyst. During the 1920's and 1930's, chemists [2][3][4][5][6][7][8] conducted a large number of experimental and theoretical studies with regards to the acid-catalyzed carboxylic acid esterification mechanism. At that time, an important question regarding the mechanism was the origin of the alkyl-oxygen in the formation of the ester.…”
Section: Introductionmentioning
confidence: 99%
“…This is analogous to the Fischer− Speier mechanism described for esterification reactions involving carboxylic acids and alcohols. 42 Urey and Roberts 43 demonstrated that reacting 18 O-labeled methyl alcohol with benzoic acid results in a 18 O-labeled methyl benzoate ester. Thus, the condensed water molecule produced in this reaction contained the oxygen from benzoic acid.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
“…These pioneer workers showed that in the alkaline hydrolysis of amyl acetate, substitution takes place at the carbonyl rather than alkyl carbon. Roberts & Urey (106) showed that in the esterification of benzoic acid by CHaOH in acid, again the alkyl oxygen bond is preserved. Datta, Day & Ingold (42) showed that the methyl-oxygen bond remains intact in the alkaline hydrolysis of methyl succinate.…”
Section: Miscellaneous Exchange Reactionsmentioning
confidence: 99%